Investigation of Sludge Gasification under Flue Gas. (October 2018) - Weng, Zhouchao; Lin, Jie; Yan, Mi; Su, Hongcai; Zhang, Sicheng; Wang, Guobin; Kanchanatip, Ekkachai
Abstract: This paper presents the study of sludge gasification under different model flue gases for supporting the development of dual bed gasifier. There are three model gases including 16%O2 /N2, 16%O2 /20%CO2 /N2 and 16%O2 /20%CO2 /40%H2 O/N2, as well as fly ash containing groups. The combustible gas yields were in the range of 247.8–417.3 L/kg sludge, the heating values of the producer gas were in a range of 2, 881.8–6, 617.3 kJ/m 3, and the gasification efficiency were in a range of 46.43–74.56%. CO2 and H2 O had beneficial effect on combustible gas yield, gasification efficiency, and LHV of the producer gas. CO content increased while the content of H2 decreased after CO2 introduction. When H2 O was added into model gas with the ratio of 40%, H2 concentration in producer gas was remarkably increased as well as improved the overall yield, gasification efficiency, and thus resulting in a gas with a higher LHV. On the other hand, sludge fly ash added in the gasification atmosphere had a negatively effect on combustible gas yield, causing lower heating value of the producer gas. Based on the monitoring of gasification process, the LHV of produce gas can increase 2 to 3 times, possibly up to 17 MJ/m 3 by controlling the proper reaction time. The findings can lead to the optimal design of gasifier and reaction to produce high value clean energy.